2018
DOI: 10.1007/s10551-018-3982-3
|View full text |Cite
|
Sign up to set email alerts
|

Boiling the Frog Slowly: The Immersion of C-Suite Financial Executives into Fraud

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 75 publications
0
24
0
1
Order By: Relevance
“…Second, in broadening our understanding of self-motivations on exploring grey areas that open chances to commit fraud, this study offers interesting theoretical perspectives from the social psychology, which is relatively clouded and shallow, as responses to Suh et al (2018). Suh et al argue that very few studies have identified societal pressures and contexts as causes behind the emergence of workplace cultures that foster fraudulent behaviours.…”
Section: Significance Of Researchmentioning
confidence: 98%
See 1 more Smart Citation
“…Second, in broadening our understanding of self-motivations on exploring grey areas that open chances to commit fraud, this study offers interesting theoretical perspectives from the social psychology, which is relatively clouded and shallow, as responses to Suh et al (2018). Suh et al argue that very few studies have identified societal pressures and contexts as causes behind the emergence of workplace cultures that foster fraudulent behaviours.…”
Section: Significance Of Researchmentioning
confidence: 98%
“…First and foremost, our study identifies critical antecedents that strongly provide the motivational impetus for individuals' intentions to perpetrate fraud. It implies, before individualised micro psychology motivate him or her to form an intention to fraud (Akkeren and Buckby, 2017;Suh et al, 2018;Free and Murphy, 2015;Trompeter et al, 2013), the motivational state of mind wherein appraisals and reasons to act are much more influenced by situational variables within organisation and external organisations.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Despite the importance of psychological characteristics of an individual in the understanding of some of the root causes of fraud, it is also imperative to explore the connection between the characteristics of the sociological organisation and the employees' decisions to engage in fraudulent behaviours. There are some studies that have shed light on the individualised and structural aspects of fraud (Suh et al, 2018;Lokanan, 2018;Belle and Cantarelli, 2017;Schuchter and Levi, 2015;Soltani, 2014;Morales et al, 2014), but they have not examined the routines of interaction both micro-constructs and social psychological constructs in studying fraudulent behaviours within an organisation. Some scholars noted that we need a theoretical stance as to why (honest) people engage in the circle of fraudulent behaviours, which looks at the interplay between micro-and macro-factors (Lokanan, 2018;Akkeren and Buckby, 2017;Anand et al, 2015).…”
Section: Directions For Future Researchtheoretical Implicationsmentioning
confidence: 99%
“…In analysis of individuals' tendencies to defraud, the extent to which the group members are mutually dependent upon each other to reach a certain goal can also form strongest triggers than sociological and financial ones (Suh et al, 2018), without affecting the presence of opportunity to do fraud. These results are consistent with prior studies carried out by Benson et al (2009), Schuchter and Levi (2015) and Albrecht et al (2004) who claim that opportunities and financial needs are not mandatory factors provoking a person to commit fraud.…”
Section: Theoretical Implicationsmentioning
confidence: 99%